Geosite and Geomorphosite Assessment for Geotourism Purpose: Case Study of the Islands in Kwandang Bay, North Gorontalo - Intan Noviantari Manyoe; Yayu Isyana Pongoliu; Siti Suhartini S. Napu (Tunas Geografi, 2022)
Gorontalo's geological diversity can be utilized for the development of geotourism, but the study of geotourism in Gorontalo has not been carried out comprehensively. The purpose of this study is to assess the geosite and geomorphosite of islands in Kwandang Bay, North Gorontalo, namely Ponelo Island, Saronde Island, Bogisa Island, and Hulawa Island. Stages of research include the stage of field data collection through geological surveys, processing, and data analysis. Geosite and geomorphosite assessments use the Kubalikova method. The results showed that there were eight sites on the islands, namely basalt cliffs, wave-cut platforms, tombolo, Saronde white sand, spit, andesite, and Hulawa white sand. The highest score gotten by Ponelo Island and Bogisa Island is on the economic value due to its good accessibility. The highest score of Saronde Island is on educational value because it has a geotourism aspect and is a public visited place. The highest score for Hulawa Island is the additional value because there are aspects of history and archeology of the Netherland colonial. The total values of geosite and geomorphosite assessment in Ponelo, Saronde, Bogisa, and Hulawa Island consecutively are 7.5, 8.5, 6.5, and 8.5. Geosite and geomorphosite on the islands in Kwandang Bay are valuable in terms of scientific, educational, conservation, economic and additional value.Key words: Marine landforms, Geology, Geomorphology, Culture.